Ultra-light magnesium-lithium alloy based on in-situ synthesis nanophase enhancement and preparation method of ultra-light magnesium-lithium alloy
By introducing in-situ self-generating nanophase into ultralight magnesium lithium alloys, combined with specific element ratios and process processing, the problem of the decrease in tensile strength after long-term placement of the alloy is solved, and high performance stability and low density magnesium lithium are achieved alloy.
Patent Information
- Application Number
- CN202411603338.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The tensile strength of ultralight magnesium lithium alloys decreases significantly after long-term placement, resulting in insufficient performance stability.
Using ultralight magnesium lithium alloy based on in-situ self-generating nanophase enhancement, the α-Mg phase, β-Li phase, MgLi2Al phase, in-situ self-generating nanophase enhancement, and rare earth-rich phase is formed through specific element ratios and process treatments. The nano AlLi phase was recharged and analyzed first to inhibit the formation of softened phase.
The performance stability of the alloy is effectively improved. After two years of storage, the performance remains above 95%, the density is less than 1.55g/cm3, and the room temperature tensile strength and elongation after break are significantly improved.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magnesium-lithium alloy preparation, and in particular relates to an ultralight magnesium-lithium alloy based on in-situ self-generated nanophase reinforcement and a preparation method thereof. Background Art
[0002] The specific gravity of ultra-light magnesium-lithium alloy is between 1.4 and 1.6, which is slightly higher than the density of plastic. The strength is usually 220~340MPa. It has high damping, which is more than ten times that of aluminum alloy. It can absorb impact energy and has good shock absorption and noise reduction effects. It can be formed by plastic processing at room temperature, cast and semi-solid injection molding, which is conducive to the application of lightweight metals.
[0003] The existing document CN107779708B discloses a high-strength ultra-light magnesium-lithium alloy, which is composed of the following mass percentages: Li: 5-9wt.%, Nd: 4-6wt.%, Ni: 2-4wt.%, Mn: 1-2wt.%, and the balance is Mg and inevitable impurity elements; wherein the inevitable impurity elements are mainly Fe, Cu, Si, etc., with a total amount of ≤0.03%. Although the performance of the ultra-light magnesium-lithium alloy is improved compared with the mechanical properties of conventional ultra-light magnesium-lithium alloys, its tensile strength decreases significantly after long-term storage. Summary of the invention
[0004] The present invention aims to provide an ultralight magnesium-lithium alloy based on in-situ self-generated nanophase reinforcement and a preparation method thereof, which effectively solves the problem that the tensile strength of the ultralight magnesium-lithium alloy decreases significantly after being placed for a long time.
[0005] The present invention adopts the following technical solution.
[0006] An ultralight magnesium-lithium alloy based on in-situ self-generated nanophase reinforcement, wherein the mass percentage of each element is: Li accounts for 9-12%, Al accounts for 2-3.5%, Nd accounts for 0.5-1%, Er accounts for 0.15%-0.5%, Dy accounts for 0.05-0.2%, Y accounts for 0.5-1.5%, Zr accounts for 0.1-0.5%, Zn accounts for 0.5-1.5%, La accounts for 0.1-0.5%, and the balance is Mg and unavoidable impurities; wherein the total amount of rare earth elements is below 2wt.%; the ultralight magnesium-lithium alloy mainly comprises α-Mg phase, β-Li phase, MgLi2Al phase, in-situ self-generated nano AlLi phase, and rare earth-rich phase.
[0007] As one of the preferred options, Li accounts for 11.5%, Al accounts for 2.1%, Nd accounts for 0.6%, Er accounts for 0.3%, Dy accounts for 0.15%, Y accounts for 0.6%, Zr accounts for 0.3%, Zn accounts for 0.8%, La accounts for 0.2%, and the balance is Mg and unavoidable impurities.
[0008] As the second preferred option, Li accounts for 9.5%, Al accounts for 1.9%, Nd accounts for 0.8%, Er accounts for 0.4%, Dy accounts for 0.2%, Y accounts for 0.9%, Zr accounts for 0.5%, Zn accounts for 1%, La accounts for 0.5%, and the balance is Mg and unavoidable impurities.
[0009] The method for preparing the aforementioned ultra-light magnesium-lithium alloy comprises the following steps: S1. Vacuum melting: the ingredients are prepared according to the mass percentage of each component in the alloy, and the alloy is melted in a vacuum induction melting furnace. Argon protection is maintained throughout the process. The melt is stirred to make it uniform, and then cast into a single ingot mold to obtain an ingot; S2, homogenization treatment, placing the obtained ingot in a vacuum heat treatment furnace for homogenization treatment at (380°C~400°C)×(8h~12h); S3, open forging, removing the outer oxide scale of the ingot after homogenization treatment, and performing open forging; the open forging process is three-piercing and three-drawing, the mold temperature is 320°C, the billet is kept in a heat treatment furnace at 300°C for 3h before forging, the piercing and drawing ratio is 1.54, and finally a forging billet with a diameter of 220-240mm is prepared; S4, extrusion, the obtained forging billet is turned to remove the outer oxide scale, and turned into a round ingot with a diameter not greater than 240mm; the extrusion die and the forging billet are placed in a 250℃ holding furnace for 1.5~2h, and then taken out and extruded by an extruder to obtain an extruded rod, the extrusion ratio is (16~20):1, and the extrusion rate is 0.5~1mm / s; S5. Heat treatment: placing the obtained extruded rod in a heat treatment furnace for (50-100)°C × (40-120)h insulation and then water cooling, so that the nano-AlLi phase is preferentially fully precipitated and the formation of the softening phase such as MgLiZn or MgLiAl is inhibited.
[0010] The method for preparing a light magnesium-lithium alloy corresponding to one of the above-mentioned super preferred schemes comprises the following steps: S11, vacuum melting, the ingredients are prepared according to the mass percentage of each component in the alloy, and the alloy is melted in a vacuum induction melting furnace, and argon protection is maintained throughout the process; first, pure magnesium, pure lithium, pure aluminum, and Mg-30Y, Mg-30Nd, Mg-30Zr, Mg-30La, Mg-30Dy, Mg-30Er, and Mg-30Zn intermediate alloys are placed in a crucible, and YAl2 particles are added after they are melted, and then a combination of physical stirring and ultrasonic stirring is used to make the melt uniform, and then cast it into a single ingot mold; S12, homogenization treatment, placing the obtained ingot in a vacuum heat treatment furnace for homogenization treatment at 400° C.×12 h; S13, open forging, removing the outer oxide scale of the ingot after homogenization treatment, and performing open forging; the open forging process is three-piercing and three-drawing, the mold temperature is 320° C., the billet is kept in a heat treatment furnace at 300° C. for 3 hours and then forged, the piercing and drawing ratio is 1.54, and finally a forging billet with a diameter of 220 mm is prepared; S14, extrusion, the obtained forging billet is turned to remove the outer oxide scale, and turned into a round ingot with a diameter not greater than 240 mm; the extrusion die and the forging billet are placed in a 250°C insulation furnace for 2 hours, and then taken out and extruded by a 600t extruder to obtain an extruded rod, the extrusion ratio is 20:1, and the extrusion rate is 0.5 mm / s; S15, heat treatment, placing the obtained extruded rod in a heat treatment furnace for insulation at 100°C for 100h and then water cooling to allow the nano-AlLi phase to be fully precipitated.
[0011] The preparation method of the light magnesium-lithium alloy corresponding to the second super preferred solution comprises the following steps: S11, vacuum melting, the ingredients are prepared according to the mass percentage of each component in the alloy, and the alloy is melted in a vacuum induction melting furnace, and argon protection is maintained throughout the process; first, pure magnesium, pure lithium, pure aluminum, Mg-30Y, Mg-30Nd, Mg-30Zr and other intermediate alloys are placed in a crucible, and YAl2 particles are added after they are melted, and then a combination of physical stirring and ultrasonic stirring is used to make the melt uniform, and then cast it into a single ingot mold; S12, homogenization treatment, placing the obtained ingot in a vacuum heat treatment furnace for homogenization treatment at 400° C.×11.5 h; S13, open forging, removing the outer oxide scale of the ingot after homogenization treatment, and performing open forging; the open forging process is three-piercing and three-drawing, the mold temperature is 320° C., the billet is kept in a heat treatment furnace at 310° C. for 3 hours and then forged, the piercing and drawing ratio is 1.54, and finally a forging billet with a diameter of 220 mm is prepared; S14, extrusion, the obtained forging billet is turned to remove the outer oxide scale, and turned into a round ingot with a diameter not greater than 240 mm; the extrusion die and the forging billet are placed in a 250°C insulation furnace for 2 hours, and then taken out and extruded by a 600t extruder to obtain an extruded rod, the extrusion ratio is 20:1, and the extrusion rate is 0.5 mm / s; S15, heat treatment, placing the obtained extruded rod in a heat treatment furnace for insulation at 50°C for 50h and then water cooling.
[0012] Beneficial effects: The process of the present invention is simple and can be industrially produced and applied. The magnesium-lithium alloy prepared by the scheme of the present invention has the advantages of being ultra-light (density less than 1.55g / cm 3), high plasticity (room temperature elongation after fracture is more than 40%), high stability (performance remains more than 95% after two years of placement), etc. The present invention effectively reduces the density of the alloy, which has a significant effect on improving the mobility of the components, and the presence of β-Li can greatly improve the deformation capacity and elongation of the alloy, laying the foundation for the application of this material in various special-shaped and complex components; at the same time, through the synergistic effect of multiple rare earth elements and AlY2, the solid solution strengthening and precipitation strengthening effects are fully exerted, so that the alloy maintains ultra-low density while improving the strength of the alloy; through the joint cooperation of alloy composition optimization and subsequent specific aging stabilization treatment, the nano-AlLi phase is promoted to be fully precipitated first, and the formation of softening phases such as MgLiZn or MgLiAl is hindered, which effectively increases the performance stability of the alloy and solves the significant performance attenuation problem currently faced by magnesium-lithium alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is the bright field TEM image of the nano-AlLi phase in Example 1. DETAILED DESCRIPTION
[0014] The technical solution of the present invention is described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0015] An ultralight magnesium-lithium alloy based on in-situ self-generated nanophase reinforcement, wherein the mass percentage of each element is: Li accounts for 11.5%, Al accounts for 2.1%, Nd accounts for 0.6%, Er accounts for 0.3%, Dy accounts for 0.15%, Y accounts for 0.6%, Zr accounts for 0.3%, Zn accounts for 0.8%, La accounts for 0.2%, and the balance is Mg and unavoidable impurities; the ultralight magnesium-lithium alloy mainly comprises α-Mg phase, β-Li phase, MgLi2Al phase, in-situ self-generated nano-AlLi phase, and rare earth-rich phase.
[0016] The method for preparing the ultralight magnesium-lithium alloy in this embodiment comprises the following steps: S11, vacuum melting, the ingredients are prepared according to the mass percentage of each component in the alloy, and the alloy is melted in a vacuum induction melting furnace, and argon protection is maintained throughout the process; first, pure magnesium, pure lithium, pure aluminum, Mg-30Y, Mg-30Nd, Mg-30Zr and other intermediate alloys are placed in a crucible, and YAl2 particles are added after they are melted, and then a combination of physical stirring and ultrasonic stirring is used to make the melt uniform, and then cast it into a single ingot mold; S12, homogenization treatment, placing the obtained ingot in a vacuum heat treatment furnace for homogenization treatment at 400° C.×12 h; S13, open forging, removing the outer oxide scale of the ingot after homogenization treatment, and performing open forging; the open forging process is three-piercing and three-drawing, the mold temperature is 320° C., the billet is kept in a heat treatment furnace at 300° C. for 3 hours and then forged, the piercing and drawing ratio is 1.54, and finally a forging billet with a diameter of 220 mm is prepared; S14, extrusion, the obtained forging billet is turned to remove the outer oxide scale, and turned into a round ingot with a diameter not greater than 240 mm; the extrusion die and the forging billet are placed in a 250°C insulation furnace for 2 hours, and then taken out and extruded by a 600t extruder to obtain an extruded rod, the extrusion ratio is 20:1, and the extrusion rate is 0.5 mm / s; S15, heat treatment, placing the obtained extruded rod in a heat treatment furnace for 100°C × 100h insulation and then water cooling, so that the nano-AlLi phase is fully precipitated, such as Figure 1 As shown, (a), (b), and (c) are bright field transmission images of nano-AlLi phase.
[0017] The performance and density of the ultra-light magnesium-lithium alloy prepared in this embodiment are as follows: density 1.48 g / cm 3 The tensile strength at room temperature is 180MPa and the elongation at break is 58%; after one year of storage, the tensile strength remains above 170MPa. Example 2
[0018] An ultralight magnesium-lithium alloy based on in-situ self-generated nanophase reinforcement, wherein the mass percentage of each element is: Li accounts for 9.5%, Al accounts for 1.9%, Nd accounts for 0.8%, Er accounts for 0.4%, Dy accounts for 0.2%, Y accounts for 0.9%, Zr accounts for 0.5%, Zn accounts for 1%, La accounts for 0.5%, and the balance is Mg and unavoidable impurities.
[0019] The method for preparing the ultralight magnesium-lithium alloy in this embodiment comprises the following steps: S11, vacuum melting, the ingredients are prepared according to the mass percentage of each component in the alloy, and the alloy is melted in a vacuum induction melting furnace, and argon protection is maintained throughout the process; first, pure magnesium, pure lithium, pure aluminum, Mg-30Y, Mg-30Nd, Mg-30Zr and other intermediate alloys are placed in a crucible, and YAl2 particles are added after they are melted, and then a combination of physical stirring and ultrasonic stirring is used to make the melt uniform, and then cast it into a single ingot mold; S12, homogenization treatment, placing the obtained ingot in a vacuum heat treatment furnace for homogenization treatment at 400° C.×11.5 h; S13, open forging, removing the outer oxide scale of the ingot after homogenization treatment, and performing open forging; the open forging process is three-piercing and three-drawing, the mold temperature is 320° C., the billet is kept in a heat treatment furnace at 310° C. for 3 hours and then forged, the piercing and drawing ratio is 1.54, and finally a forging billet with a diameter of 220 mm is prepared; S14, extrusion, the obtained forging billet is turned to remove the outer oxide scale, and turned into a round ingot with a diameter not greater than 240 mm; the extrusion die and the forging billet are placed in a 250°C insulation furnace for 2 hours, and then taken out and extruded by a 600t extruder to obtain an extruded rod, the extrusion ratio is 20:1, and the extrusion rate is 0.5 mm / s; S15, heat treatment, placing the obtained extruded rod in a heat treatment furnace for insulation at 50°C for 50 hours and then water cooling to allow the nano-AlLi phase to be fully precipitated.
[0020] The performance and density of the ultra-light magnesium-lithium alloy prepared in this embodiment are as follows: density 1.53 g / cm 3 The tensile strength at room temperature is 224MPa, the elongation at break is 41%, and the tensile strength remains above 200MPa after one year of storage.
[0021] The magnesium-lithium alloy produced by the specific ratio composition and specific process in the present invention has the characteristics of ultra-light (density less than 1.55g / cm 3 ), high plasticity (elongation after break at room temperature is more than 40%), high stability (performance remains more than 95% after two years of storage) and other advantages.
Claims
1. An ultralight magnesium-lithium alloy based on in-situ self-generated nanophase reinforcement, characterized in that: The mass percentage of each element is: Li accounts for 9-12%, Al accounts for 2-3.5%, Nd accounts for 0.5-1%, Er accounts for 0.15%-0.5%, Dy accounts for 0.05-0.2%, Y accounts for 0.5-1.5%, Zr accounts for 0.1-0.5%, Zn accounts for 0.5-1.5%, La accounts for 0.1-0.5%, and the balance is Mg and inevitable impurities; wherein the total amount of rare earth elements is less than 2wt.%; the ultra-light magnesium-lithium alloy mainly includes α-Mg phase, β-Li phase, MgLi2Al phase, in-situ self-generated nano-AlLi phase, and rare earth-rich phase.
2. The ultralight magnesium-lithium alloy according to claim 1, characterized in that: Li accounts for 11.5%, Al accounts for 2.1%, Nd accounts for 0.6%, Er accounts for 0.3%, Dy accounts for 0.15%, Y accounts for 0.6%, Zr accounts for 0.3%, Zn accounts for 0.8%, La accounts for 0.2%, and the balance is Mg and unavoidable impurities.
3. The ultralight magnesium-lithium alloy according to claim 1, characterized in that: Li accounts for 9.5%, Al accounts for 1.9%, Nd accounts for 0.8%, Er accounts for 0.4%, Dy accounts for 0.2%, Y accounts for 0.9%, Zr accounts for 0.5%, Zn accounts for 1%, La accounts for 0.5%, and the balance is Mg and unavoidable impurities.
4. The method for preparing the ultralight magnesium-lithium alloy according to any one of claims 1 to 3, characterized in that the steps include: S1. Vacuum melting: the ingredients are prepared according to the mass percentage of each component in the alloy, and the alloy is melted in a vacuum induction melting furnace. Argon protection is maintained throughout the process. The melt is stirred to make it uniform, and then cast into a single ingot mold to obtain an ingot; S2, homogenization treatment, placing the obtained ingot in a vacuum heat treatment furnace for homogenization treatment at (380°C~400°C)×(8h~12h); S3, open forging, removing the outer oxide scale of the ingot after homogenization treatment, and performing open forging; the open forging process is three-piercing and three-drawing, the mold temperature is 320°C, the billet is kept in a heat treatment furnace at 300°C for 3h before forging, the piercing and drawing ratio is 1.54, and finally a forging billet with a diameter of 220-240mm is prepared; S4, extrusion, the obtained forging billet is turned to remove the outer oxide scale, and turned into a round ingot with a diameter not greater than 240mm; the extrusion die and the forging billet are placed in a 250℃ holding furnace for 1.5~2h, and then taken out and extruded by an extruder to obtain an extruded rod, the extrusion ratio is (16~20):1, and the extrusion rate is 0.5~1mm / s; S5. Heat treatment: placing the obtained extruded rod in a heat treatment furnace for (50-100)℃×(40-120)h insulation and then water cooling, so that the nano-AlLi phase is preferentially and fully precipitated and the formation of the softening phase is inhibited.
5. The method for preparing the ultralight magnesium-lithium alloy according to claim 2, characterized in that the steps include: S11, vacuum melting, the ingredients are prepared according to the mass percentage of each component in the alloy, and the alloy is melted in a vacuum induction melting furnace, and argon protection is maintained throughout the process; first, pure magnesium, pure lithium, pure aluminum, and Mg-30Y, Mg-30Nd, Mg-30Zr, Mg-30La, Mg-30Dy, Mg-30Er, and Mg-30Zn intermediate alloys are placed in a crucible, and YAl2 particles are added after they are melted, and then a combination of physical stirring and ultrasonic stirring is used to make the melt uniform, and then cast it into a single ingot mold; S12, homogenization treatment, placing the obtained ingot in a vacuum heat treatment furnace for homogenization treatment at 400° C.×12 h; S13, open forging, removing the outer oxide scale of the ingot after homogenization treatment, and performing open forging; the open forging process is three-piercing and three-drawing, the mold temperature is 320° C., the billet is kept in a heat treatment furnace at 300° C. for 3 hours and then forged, the piercing and drawing ratio is 1.54, and finally a forging billet with a diameter of 220 mm is prepared; S14, extrusion, the obtained forging billet is turned to remove the outer oxide scale, and turned into a round ingot with a diameter not greater than 240 mm; the extrusion die and the forging billet are placed in a 250°C insulation furnace for 2 hours, and then taken out and extruded by a 600t extruder to obtain an extruded rod, the extrusion ratio is 20:1, and the extrusion rate is 0.5 mm / s; S15, heat treatment, placing the obtained extruded rod in a heat treatment furnace for insulation at 100°C for 100h and then water cooling to allow the nano-AlLi phase to be fully precipitated.
6. The method for preparing the ultralight magnesium-lithium alloy according to claim 3, characterized in that the steps include: S11, vacuum melting, the ingredients are prepared according to the mass percentage of each component in the alloy, and the alloy is melted in a vacuum induction melting furnace, and argon protection is maintained throughout the process; first, pure magnesium, pure lithium, pure aluminum, Mg-30Y, Mg-30Nd, Mg-30Zr and other intermediate alloys are placed in a crucible, and YAl2 particles are added after they are melted, and then a combination of physical stirring and ultrasonic stirring is used to make the melt uniform, and then cast it into a single ingot mold; S12, homogenization treatment, placing the obtained ingot in a vacuum heat treatment furnace for homogenization treatment at 400° C.×11.5 h; S13, open forging, removing the outer oxide scale of the ingot after homogenization treatment, and performing open forging; the open forging process is three-piercing and three-drawing, the mold temperature is 320° C., the billet is kept in a heat treatment furnace at 310° C. for 3 hours and then forged, the piercing and drawing ratio is 1.54, and finally a forging billet with a diameter of 220 mm is prepared; S14, extrusion, the obtained forging billet is turned to remove the outer oxide scale, and turned into a round ingot with a diameter not greater than 240 mm; the extrusion die and the forging billet are placed in a 250°C insulation furnace for 2 hours, and then taken out and extruded by a 600t extruder to obtain an extruded rod, the extrusion ratio is 20:1, and the extrusion rate is 0.5 mm / s; S15, heat treatment, placing the obtained extruded rod in a heat treatment furnace for insulation at 50°C for 50h and then water cooling.
Citation Information
Patent Citations
A high-strength, ultralight magnesium-lithium alloy and its preparation method
CN107779708B